Stronger Arctic amplification from ozone-depleting substances than from carbon dioxide - Liang, Yu-Chiao; Polvani, Lorenzo M.; Previdi, Michael; Smith, Karen L.; England, Mark R.; Chiodo, Gabriel; id_orcid:0 000-0002-8079-6314 (IOP Publishing, 2022)
Arctic amplification (AA)-the greater warming of the Arctic near-surface temperature relative to its global mean value-is a prominent feature of the climate response to increasing greenhouse gases. Recent work has revealed the importance of ozone-depleting substances (ODS) in contributing to Arctic warming and sea-ice loss. Here, using ensembles of climate model integrations, we expand on that work and directly contrast Arctic warming from ODS to that from carbon dioxide (CO2), over the 1955-2005 period when ODS loading peaked. We find that the Arctic warming and sea-ice loss from ODS are slightly more than half (52%-59%) those from CO2. We further show that the strength of AA for ODS is 1.44 times larger than that for CO2, and that this mainly stems from more positive Planck, albedo, lapse-rate, and cloud feedbacks. Our results suggest that AA would be considerably stronger than presently observed had the Montreal Protocol not been signed. ISSN:1748-9326 ISSN:1748-9318